Digitally-mediated coordination in healthcare: the effects of teleconsultation on doctor-to-doctor relational coordination - Mattia Vincenzo Olive; Luca Gastaldi; Mariano Corso (BMC Health Services Research, 2024)
Abstract Background Digitalization transforms the way in which interdependent work is coordinated, especially in healthcare settings. This work deepens the effect of teleconsultation use on health professionals’ coordination. For this aim, we rely on Relational Coordination Theory (RCT), which explores coordination as an interactive process among group participants within the context of task interdependency. Methods We collected data through an online survey administered to Italian specialist doctors between March and April 2023. 489 complete answers were gathered. Hypotheses have been tested through Structural Equation Modelling. Results We found that teleconsultation frequency of use has a positive and significant effect on both components of relational coordination, confirming our hypotheses. Conclusions Theoretically, this research contributes to our understanding of the effect of digitally mediated coordination mechanisms on relational coordination. In practice, we shed light on the organizational implications of telemedicine under a novel perspective, focusing on the role of professional interactions in digitally mediated work and providing useful elements for the organizational design of telemedicine.